Longer Cochlear Implant Experience Leads to Better Production of Mandarin Tones for Early Implanted Children. Issue 5 (September 2021) - Tang, Ping; Yuen, Ivan; Xu Rattanasone, Nan; Gao, Liqun; Demuth, Katherine
Abstract : Objectives: Children with cochlear implants (CIs) face challenges in acquiring tones, since CIs do not transmit pitch information effectively. It has been suggested that longer CI experience provides additional benefits for children implanted early, enabling them to achieve language abilities similar to that of normal-hearing (NH) children (Colletti 2009 ). Mandarin is a tonal language with four lexical tones and a neutral tone (T0), characterized by distinct pitch and durational patterns. It has been suggested that early implantation (i.e., before 2 years) greatly benefits the acquisition of Mandarin tones by children with CIs (Tang et al. 2019c ). In this study, we extend those findings to investigate the effect of CI experience on the acquisition of Mandarin tones for children implanted early. We asked the extent to which they were able to produce distinct pitch and durational patterns of both lexical tones and T0 as a function of CI experience, and the extent to which their tonal productions were acoustically like that of NH children. Design: Forty-four NH 3-year olds and 28 children implanted with CIs between 1 and 2 years, aged 3 to 7, were recruited. The children with CIs were grouped according to the length of CI experience: 3 to 6 years, 2 to 3 years, and 1 to 2 years. Lexical tone and T0 productions were elicited using a picture-naming task. Tonal productions from the children with CIs were acoustically analyzed and compared with those from the NH children. Results: Children with 3 to 6 years of CI experience were able to produce distinct pitch and durational patterns for both lexical tones and T0, with NH-like acoustic realizations. Children with 2 to 3 years of CI experience were also able to produce the expected tonal patterns, although their productions were not yet NH-like. Those with only 1 to 2 years of CI experience, however, were not yet able to produce the distinct acoustic patterns for either lexical tones or T0. Conclusions: These results provide acoustic evidence demonstrating that, when Mandarin-speaking children are implanted before the age of 2, only those with 3 to 6 years of experience were able to produce NH-like tones, including both lexical tone and T0. Children with shorter CI experience (less than 3 years) were unable to produce distinct acoustic patterns for the different tones. This suggests that at least 3 years of CI experience is still needed for early implanted children to acquire tonal distinctions similar to those of NH 3-year olds. Abstract : Supplemental Digital Content is available in the text.